Middleware Data Platform in Agricultural Supply Chain - Kumar, Sanjeev (ExcelingTech, 2025)
Demographic and climatic changes, changes in resource distribution and soil condition of compost, depleting water resources, greater demand for customized products, need for traceability to maintain food safety and hygiene; all warrant the use of sophisticated modern technologies all along the food supply chain (SC). The integration of IoT, AI and such other technologies with blockchain can significantly improve operational efficiency of agriculture, allowing traceability and ensuring safety and quality control. Such integration also helps to realize maximum benefits from application of modern technologies to make entire agri SC more resilient. Successful application of various technologies hinges on efficient data analytics and technology integration and can be achieved using middleware for technology integration and seamless data flow within the SC. Though promising, it presents significant challenges that need to be handled to realize its full potential. This article establishes middleware data platform’s potential in integrating AI, IoT and blockchain technologies and enhancing operational efficiency of agri SC through enhanced transparency, efficiency, and security. Using a systematic AI-driven data analytics platform Middleware provides diagnostic intelligence to the farmers. Realizing middleware’s potential and utilizing it can greatly enhance functionality and performance of ASC, making it an essential tool for both developers and users. However, the technology being nascent, there is significant dearth of data, literature and evidence regarding the user experience and success rate of middleware, hence a significant knowledge gap. This article contributes towards bridging the gap, setting the floor for further research.